Pendampingan Pengabdian Kepada Masyarakat Bagi Pengrajin Limbah Jagung di Kabupaten Pati - Sri Mulyani; Budi Gunawan; Mukhamad Nurkamid (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
There are many types of handicrafts from Pati Regency, one of which is corncob crafts whose raw materials come from unused corn waste. The corncobs are processed into various forms of crafts including night lamps, watches, tissue holders, jars, flower holders, wall hangings and much more. The COVID-19 pandemic caused SMEs to experience a decline in sales. In order to help increase sales, the service team carried out several mentoring activities. Some of the mentoring activities carried out are providing training and e-marketing assistance, determining selling prices, and recording financials through the android application. Participants in community service activities are UKM